Innateness of Activity and Their Development - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2004)
The article evaluates some innate features of human activeness: three forms of activities (play, learning, and work), intellect and creativity. Empirical research has demonstrated that Lithuanian students of social work and pre-school pedagogy do not apply their own possibilities to learning. The standards of teaching for secondary schools do not take sufficient requirements for intellectual training. The article also examines some educational methods of the development of innate activity.